2021
DOI: 10.2147/cmar.s286269
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy Risk Stratification Prediction of Amorphous Calcifications Based on Clinical and Mammographic Features

Abstract: To explore the potential factors influencing the malignancy risk of amorphous calcifications and establish a predictive nomogram for malignancy risk stratification. Patients and Methods: Consecutive mammograms from January 2013 to December 2018 were retrospectively reviewed. Traditional clinical features were recorded, and mammographic features were estimated according to the 5th BI-RADS. Included calcifications were randomly divided into the training and validation cohorts. A nomogram was developed to graphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Many factors affect the PPV of calcifications, including the distribution, morphology, patient age/ menopausal status, whether the mammogram was for screening or diagnostic purposes, and history of breast or ovarian cancer (2)(3)(4)(5)(6)(7)(8)(9)(10)14,15). We also found that the malignancy rate of grouped amorphous calcifications was lower than other calcification distributions in our previous study (16). However, to date, very few studies have focused on the assessment of pure grouped amorphous calcifications.…”
Section: Introductionsupporting
confidence: 62%
“…Many factors affect the PPV of calcifications, including the distribution, morphology, patient age/ menopausal status, whether the mammogram was for screening or diagnostic purposes, and history of breast or ovarian cancer (2)(3)(4)(5)(6)(7)(8)(9)(10)14,15). We also found that the malignancy rate of grouped amorphous calcifications was lower than other calcification distributions in our previous study (16). However, to date, very few studies have focused on the assessment of pure grouped amorphous calcifications.…”
Section: Introductionsupporting
confidence: 62%
“…In recent years, screening programmes advocate a high call-back biopsy rate, arousing controversies on the acceptable malignancy risk and critics on unnecessary biopsies and misallocated healthcare resources. 2,3,6 Apart from recent evidence supporting a lower BI-RADS subcategory as discussed above, the majority of the malignancies come back as DCIS, which is known to carry a high survival rate after surgical and optional adjuvant treatments. 2,3 This is also coherent with our results, with 80% (n = 4) of malignant cases being DCIS.…”
Section: Discussionmentioning
confidence: 99%